Oral Semaglutide in the Management of Type 2 DM: Clinical Status and Comparative Analysis - Bandyopadhyay, Ilora; Dave, Sunny; Rai, Amita; Nampoothiri, Madhavan; Chamallamudi, Mallikarjuna R.; Kumar, Nitesh (Current Drug Targets, 2022)
Background: In the incretin system, Glucagon-like peptide-1 (GLP-1) is a hormone that inhibits the release of glucagon and regulates glucose-dependent insulin secretion. In type 2 diabetes, correcting the impaired incretin system using GLP-1 agonist is a well-defined therapeutic strategy. Objectives: This review article aims to discuss the mechanism of action, key regulatory events, clinical trials for glycaemic control, and comparative analysis of semaglutide with the second-line antidiabetic drugs. Description: Semaglutide is a glucagon-like peptide 1 (GLP-1) receptor agonist with enhanced glycaemic control in diabetes patients. In 2019, USFDA approved the first oral GLP-1 receptor agonist, semaglutide, to be administered as a once-daily tablet. Further, recent studies highlight the ability of semaglutide to improve Glycemic control in obese patients with a reduction in body weight. Still, in clinical practice, in the type 2 DM treatment paradigm, the impact of oral semaglutide remains unidentified. This review article discusses the mechanism of action, pharmacodynamics, key regulatory events, and clinical trials regarding glycaemic control. Conclusion: The review highlights the comparative analysis of semaglutide with the existing second- line drugs for the management of type 2 diabetes mellitus by stressing its benefits and adverse events.
Keywords: GLP-1 receptor agonist